Wet cultivation in lowland rice causing excess water problems for the subsequent non-rice crops in the Mekong region - Mitchell, Jaquie; Cheth, Kimngoy; Seng, Vang; Lor, Bunna; Ouk, Makara; Fukai, Shu (Field crops research, 2013)
► Wet cultivation in lowland fields causes excess water problems for non-rice crops. ► Describes water balance in the lowland fields. ► Non-rice crops often fail completely or partially due to excess water. ► Shallow root systems in the top soil above the hard pan limits productivity. ► High value crops have the potential to significantly increase farmer income. Crop diversification is advocated for improvement of income of lowland rice farmers in the Mekong region, including Laos, Cambodia and Thailand. One common problem of adding non-rice crops after wetland rice is excess water caused by reduced drainage associated with the hard pan that is commonly created to store water in the paddy for the rice crop. This paper firstly describes the water balance in the lowland fields particularly on how deep percolation is decreased by the hard pan, and the effect of wet cultivation on soil compaction and water availability in the subsequent crops such as mungbean. Experimental work in Cambodia shows how non-rice crops such as mungbean and peanut often fail completely or partially due to excess water. The common experience is complete failure of the early wet season non-rice crop when rain started earlier and the lowland paddy is saturated with water, but also non-rice crops often do not grow well due to shallow root systems confined to the top soil above the hard pan. Destructing the hard pan may help non-rice crops, but the process is expensive and may have an adverse effect on subsequent rice crops. Experimental work has also demonstrated that where irrigation water is available, irrigation is often not effective as it causes soil saturation in the top soil. Ways to minimize the excess water problem are discussed.